PERANCANGAN DESTINATION BRANDING DESA WISATA KETENGER KABUPATEN BANYUMAS UNTUK MENDUKUNG PROGRAM DIGITAL DESTINATION - Monica Revias Purwa Kusuma (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2019)
Abstract: Ketenger Tourism Village in Kab. Banyumas has very beautiful natural potential, but does not have a good branding or promotion. Image Ketenger Tourism Village needs to be improved by designing destination branding in order to change the perception of the target audience and make it an alternative tourism destination in the Banyumas regency. The method used in this research is observation, interviews, documentation, and literature studies. The purpose of this research is to increase the attractiveness of tourists to come and visit Ketenger Tourism Village while supporting the digital destination program launched by the Ministry of Tourism. The results of this study are the design of the new identity of Ketenger Tourism Village in the form of logos, banners, billboards, brochures, tickets, shirts, arches, integrated sign systems, photogenic spots, and Instagram. The conclusion of this study is that the design of destination branding in an area is one of the things that needs to be done to help implement a digital destination tourism program made by the government. Keywords: tourism, destination branding, digital destination, Ketenger Tourism Village